The Cultivable Surface Microbiota of the Brown Alga Ascophyllum nodosum is Enriched in Macroalgal-Polysaccharide-Degrading Bacteria - Martin, Marjolaine; Barbeyron, Tristan; Martin, Renee; Portetelle, Daniel; Michel, Gurvan; Vandenbol, Micheline (Frontiers in Microbiology, 2015)
Bacteria degrading algal polysaccharides are key players in the global carbon cycle and in algal biomass recycling. Yet the water column, which has been studied largely by metagenomic approaches, is poor in such bacteria and their algal-polysaccharide-degrading enzymes. Even more surprisingly, the few published studies on seaweed-associated microbiomes have revealed low abundances of such bacteria and their specific enzymes. However, as macroalgal cell-wall polysaccharides do not accumulate in nature, these bacteria and their unique polysaccharidases must not be that uncommon. We, therefore, looked at the polysaccharide-degrading activity of the cultivable bacterial subpopulation associated with Ascophyllum nodosum. From A. nodosum triplicates, 324 bacteria were isolated and taxonomically identified. Out of these isolates, 78 (~25%) were found to act on at least one tested algal polysaccharide (agar, ι- or κ-carrageenan, or alginate). The isolates “active” on algal-polysaccharides belong to 11 genera: Cellulophaga, Maribacter, Algibacter, and Zobellia in the class Flavobacteriia (41) and Pseudoalteromonas, Vibrio, Cobetia, Shewanella, Colwellia, Marinomonas, and Paraglaceciola in the class Gammaproteobacteria (37). A major part represents likely novel species. Different proportions of bacterial phyla and classes were observed between the isolated cultivable subpopulation and the total microbial community previously identified on other brown algae. Here, Bacteroidetes and Gammaproteobacteria were found to be the most abundant and some phyla (as Planctomycetes and Cyanobacteria) frequently encountered on brown algae weren’t identified. At a lower taxonomic level, twelve genera, well-known to be associated with algae (with the exception for Colwellia), were consistently found on all three A. nosodum samples. Even more interesting, 9 of the 11 above mentioned genera containing polysaccharolytic isolates were predominant in this common core. The cultivable fraction of the bacterial community associated with Ascophyllum nodosum is, thus, significantly enriched in macroalgal-polysaccharide-degrading bacteria and these bacteria seem important for the seaweed holobiont even though they are under-represented in alga-associated microbiome studies.